Prevalence of dental fluorosis and treatment needs among 11-14 years old school children in endemic fluoride areas of Haryana, India - Radhey Shyam; B C Manjunath; Adarsh Kumar; Ridhi Narang; Geeta Rani; Saumya Singh (Wolters Kluwer Medknow Publications, 2021)
Introduction: Dental fluorosis is a major endemic oral disease characterized by hypo mineralization of enamel caused due to consumption of water containing high concentration of fluoride during developmental stages of teeth. Aim: To assess the prevalence of dental fluorosis among 11-14 years old school children in endemic fluoride areas of Haryana and to find their treatment needs. Materials and Methods: A cross-sectional study was conducted among 2200 school children in endemic fluoride areas of Haryana (India) for a period of six months. Dental fluorosis was recorded by the Thylstrup-Fejerskov index (TF index) given by Thylstrup A, Fejerskov O. Statistical Analysis: Data entry and analysis were performed using Statistical Package of Social Sciences (SPSS) software version 18.0. Chi square test was used to find association between TFI scores and gender, age categories. The level of significance was set at 0.05. Results: Prevalence of dental fluorosis (TFI) reached 96.6% with most children falling in TFI score 2, 3, 4 and 5 categories. Mean TFI score of study population was found to be 3.19 ± 1.551. There was significant difference found between gender and prevalence of dental fluorosis (P = 0.00). Conclusion: Our findings showed the increased prevalence of dental fluorosis in endemic fluoride areas with mild to moderate level of dental fluorosis.